2008
DOI: 10.1074/jbc.m804488200
|View full text |Cite
|
Sign up to set email alerts
|

DNA Polymerase δ Is Highly Processive with Proliferating Cell Nuclear Antigen and Undergoes Collision Release upon Completing DNA

Abstract: In most cells, 100 -1000 Okazaki fragments are produced for each replicative DNA polymerase present in the cell. For fastgrowing cells, this necessitates rapid recycling of DNA polymerase on the lagging strand. Bacteria produce long Okazaki fragments (1-2 kb) and utilize a highly processive DNA polymerase III (pol III), which is held to DNA by a circular sliding clamp. In contrast, Okazaki fragments in eukaryotes are quite short, 100 -250 bp, and thus the eukaryotic lagging strand polymerase does not require a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
82
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(85 citation statements)
references
References 56 publications
1
82
2
Order By: Relevance
“…In the presence of polδ, the ATPγS assembled RFC · PCNA · DNA complex has been shown to support primer extension although the processivity of the replication was severely limited-tens of nucleotides vs. >5;000 nucleotides incorporated (24,39). With ATP, the key issue is which of these two populations supports holoenzyme function.…”
Section: Resultsmentioning
confidence: 99%
“…In the presence of polδ, the ATPγS assembled RFC · PCNA · DNA complex has been shown to support primer extension although the processivity of the replication was severely limited-tens of nucleotides vs. >5;000 nucleotides incorporated (24,39). With ATP, the key issue is which of these two populations supports holoenzyme function.…”
Section: Resultsmentioning
confidence: 99%
“…The assay was basically performed as described by Langston and O'Donnell (Langston & O'Donnell, 2008). ϕX174 virion circular ssDNA (0.5 nM) primed with a 70‐mer (5′‐CAAAACGGCAGAAGCCTGAATGAGCTTAATAGAGGCCAAAGCGGTCTGGAAACGTACGGATTGTTCAGTA‐3′) was incubated with PCNA (10 nM), RFC (17.5 nM), RPA (75 nM) and Polδ (10 nM) in buffer REP (20 mM Tris–HCl pH 7.5, 1 mM DTT, 12 mM MgCl 2 , 50 mM KCl, 0.1 μg/μl BSA, 0.09 μM dCTP, 0.09 μM dGTP, 1.25 mM ATP and an ATP‐regenerating system consisting of 20 mM creatine phosphate and 20 μg/ml creatine kinase) for 5 min at 30°C.…”
Section: Methodsmentioning
confidence: 99%
“…In fact, human Pol δ is known to be distributive with PCNA (25), and barring stability by another protein, quality control on the leading strand may be explained by spontaneous dissociation in humans. We note that different processivity values of S. cerevisiae Pol δ-PCNA are reported, which probably depend on the substantially different ionic strengths used in the studies, but could also possibly be due to different methods of protein preparation (12,13). It is important to note that the intracellular salt in yeast is not yet identified, nor has the intracellular ionic strength of S. cerevisiae been determined.…”
Section: Quality Control Of Polmentioning
confidence: 99%
“…However, our earlier studies made the perplexing observation that Pol e was incapable of lagging strand synthesis even in the absence of Pol δ (9, 10). We and others have shown that S. cerevisiae Pol δ-PCNA is rapid, over 100 bp/s, and its processivity varies depending on ionic strength (12,13). The intracellular ionic strength of S. cerevisiae is unknown, but at ionic strength under 70 mM, Pol δ-PCNA is highly processive for over 5 kb (13).…”
mentioning
confidence: 99%
See 1 more Smart Citation